Cold atom inertial sensors for navigation applications - Wright, Michael J.; Anastassiou, Luke; Mishra, Chinmaya; Davies, James M.; Phillips, Alexander M.; Maskell, Simon; Ralph, Jason F. (Frontiers in Physics, 2022)
Quantum sensors based on atom interferometers can provide measurements of inertial quantities with unprecedented accuracy and precision. It has been suggested that this sea change in sensing could provide an inertial navigation capability that is comparable with current satellite based navigation systems. However, the accuracy of sensor measurements is not the only factor that limits the accuracy of inertial navigation systems. In this paper, we explore the fundamental limits to inertial navigation, and explain how quantum inertial sensors could be used to alleviate some of the problems encountered in current classical inertial navigation systems, but not to solve the fundamental instability inherent in inertial navigation methods.